Acurácia e tempos de resposta de semeadora de milho à taxa variável em regimes estacionário e transitório de acionamento - Machado, Otávio Dias da Costa (2014)
This study developed routines to evaluate accuracy, longitudinal seed displacement and response times, applied to Variable Rate Technology (VRT) on seeder machines. A prototype was submitted to experiments evolving simulation, on laboratory. The experiments differed on stationary and transitory operations, with constant dosing, and along transitions of prescription maps, respectively. The evaluations were named direct, with seed placement measurement, and indirect, with rotation measurements and further variable prediction. Among four experiments, the first one focused in the stationary operation, measuring accuracy and quality of longitudinal seed displacement, using the direct evaluation method and pneumatic seed metering. In the second test, there were maintained the continuous prescription, with the indirect method and mechanical seed metering. The remaining experiments, was aimed to the transitory dosing, with indirect evaluations and pneumatic seed metering. In the third was evaluated response times, and in the fourth, the accuracy and quality of seed displacement. The results showing, by the experiments: 1) The prototype accuracy exceeds the maximum recommended value of 3%, when considering all the applied treatments. The regularity of seed displacement was proportionally affected by the influences of rotation disturbance, determined by oscillations when using specific combinations of experimental treatments and 8 and 10 km h-1 speeds. 2) Accuracy and seed displacement was degraded by the oscillations, which had a higher level than the first evaluation. The indirect evaluation, measuring the rotation, was able to describe deficiencies of the control system on the accommodation phase. 3) Response time were higher than the one second maximum value on the crescent part of transitions, when compared all treatments, but the faster crescent rate changes, lasted from 0,38 to 1,93 s. When reducing rates, 0,23 to 0,43 s times was acquired. 4) The reduction on seed displacement quality during the transitory period was expressive, in the cases which had a delayed accommodation. The prototype performance, did not attended to the maximum tolerable values. However, the verification of determined operational conditions which stability and properly accuracy, as well as fast transitions, according to the referenced values, showed that the equipment is able to a project correction process. Others results of this study, respect to preliminary experiment to the modeling process, was the identification of metering devices potential, and introduction of new methods, still not yet normalized, to the variable rate seeding evaluation.